A COMPARATIVE STUDY OF GALLIC ACID, ELLAGIC ACID, UROLITHIN A, AND UROLITHIN B WITH NF-ÎºB PROTEIN AS ANTI TYPE 2 DIABETES MELLITUS BY IN SILICO - Hikmaranti, Maulida; Astiyani, Ajeng Mareta; Hasanah, Khairul M.; Maghfiroh, Nuril M. (JSMARTech, 2020)
Abstract: Diabaetes type 2 is a common disease with clinical symptoms of abnormal insulin secretion. One of the pathways involved in the pathogenic mechanism of Type 2 Diabetes Mellitus (T2DM) is NF-?B pathway. Walnuts contain natural compounds such as gallic acid, ellagic acid, urolithin A, urolithin B and its potential to be antioxidants and anti-inflammatory. In this research, we focus on the comparative study of 4 compounds as inhibitor of NF-?B complex by molecular docking interactions between NF-?B and these ligands as a anti-T2DM compounds. The method is preparation of NF-?B protein using Discovery Studio 4.1, preparation of ligan: gallic acid, ellagic acid, urolithin, and urolithin B using Pyrx software. After that, docking protein-ligand was done by using Hex 8.0.0 software, visualized with Discovery Studio 2019 and then analyzed the bioactivity of compound through web mollinspiration, respectively. The result of mollinspiration show that 4 compounds have good quality as a drug based on the lipinski 5 rules. The docking results show that four compounds can actively bind to the active site of NF-?B with the different bond energies. Ellagic acid is the most stable compound and the highest activity to inhibition of the NF-?B pathway because its have highest binding energy than other (-228,9kcal/mol). Ellagic acid is an active polyphenol compound which is good to use as an antidepressant. Based on these comparative studies, ellagic acid has the best potential among the three other compounds in inhibiting NF-?B activity. Beside that, all compounds can effectively inhibit the activation and translocation of NF-kB from the cytoplasm to the nucleus so the NF-?B is unable to regulate DNA sequences that encode proinflammatory proteins and then be able to reduce the pathophysiological effects of type 2 diabetes mellitus.